Integrated GRC as a Risk Mitigation Effort in Company Management in the Pawn Industry to Improve the National Economy - Pariela, Eunike Petra Rebecca; Suparno (Journal Of Social Science (JoSS), 2025)
This study explores the implementation of Integrated Governance, Risk, and Compliance (GRC) as a risk mitigation strategy in the management of pawn companies to enhance the national economy. The pawn industry in Indonesia has grown significantly, offering vital financial services, particularly to micro and small enterprises. However, challenges such as weak governance, operational risks, and regulatory gaps threaten its sustainability. The research aims to analyze the role of GRC in improving corporate governance, risk management, and regulatory compliance in pawn companies, thereby contributing to economic stability and inclusivity. Using a normative legal method, the study examines laws, regulations, and theoretical frameworks related to GRC, alongside secondary data from literature and legal documents. Findings reveal that integrated GRC strengthens transparency, accountability, and risk mitigation, fostering public trust and investor confidence. It also highlights the need for clearer regulations and technological adoption to address implementation challenges. The implications of this research underscore the importance of collaborative efforts between regulators, such as the Otoritas Jasa Keuangan (OJK), and pawn companies to standardize GRC practices. By enhancing governance and compliance, the pawn industry can better support financial inclusion, SME growth, and national economic resilience.